Formation of an adaptive strategy of economic development of enterprises in the context of European integration - Shabatura, Tetyana (Management and Entrepreneurship: Trends of Development, 2019)
Purpose. The paper purpose is to research the ways of the formation of adaptive strategy of the economic development of enterprises in the context of integration and globalization processes. For this goal the following main tasks were set and solved: - the position of Ukraine in the world ranking rating according to the Global Competitiveness Index is researched; - the range of negative affection factors of economic development of domestic enterprises is determined; - the attributive filling of the adaptive strategy of economic development of the enterprise is deepening; - the scheme of adaptive concept of economic development of the enterprise in the conditions of European integration challenges is given. Design/methodology/approach. For the achievement of the mentioned purposes the general scientific methods of cognition have been used: comparison, theoretical substantiation, methods of generalization and systematization, comparative method, method of analysis and synthesis. Findings. Тhe subject of the study is theoretical and methodological aspects of the formation and implementation of an adaptive strategy of economic development of enterprises. The relevance of the question researched is coursed by the urgent need to increase the efficiency of economic development of enterprises referring to the decisive role of adaptive facilities of the enterprise in the development processes of the national economy. Today, enterprises are the key element of the national economy, whose economic development defines the level of material security of the country, satisfaction of the needs of the consumer sector, the growth of the national economy as a whole and the level of its integration into the European Union. Despite of a number of negative tendencies of European integration processes, Eurointegration will outline strategic priorities for the global economy development in the 21st century. As a conclusion, the obligatoriness of the implementing adaptive strategy of economic development of the enterprise is substantiated, which will ensure the implementation of the priority goals of its economic development in the European integration context. Research limitations/implications. The attributive filling of the adaptive strategy of economic development of the enterprise is deepened and the scheme of its realization is given in the research. Originality/value. Such knowledge will help to provide the implementation of the priority goals of economic development of the enterprise in the context of European integration. The prospect of further research is the development of a mechanism for implementing the economic potential of enterprises on the adaptability basis, that coursed by scale up of European integration processes and the integration of Ukraine into the global economic system.